The differential effects of pronunciation teaching methods of consonant sounds /p/ and /ʧ/ among Omani EFL learners - Al Yaqoobi, Zainab Mohammed Bati (2017)
This study shaded light on the differential effect of pronunciation teaching methods of consonant sounds (/p/ and /ʧ/) among Omani EFL learners. All 60 participants in the study were adults who were studying at Ibri College of Technology in Ibri, Al Dahirah Governorate. The researcher investigated the case of Ibri College of Technology students and teachers in order to compare the effectiveness of traditional teaching method (Direct Method) and customized teaching method (Minimal Pairs, Reading Aloud and Collaborative Task) in improving the participants’ pronunciation of /p/ and /ʧ/ sounds. Thus, the researcher administered diagnostic test, audio recording tests to be done by students and observation method. The study provided a theoretical description of factors affecting Omani EFL learners’ pronunciation and a review of the different methods of teaching pronunciation. The practical outcome of the study provided an analysis of data collected from the observation, diagnostic test and audio recording tests. The study successfully confirmed the hypothesis according to the interpreted results and it showed that customized teaching method was effective to improve EFL leaners’ pronunciation more than the traditional method (Direct Method). Additionally, the current study followed the mixed methods specifically the Triangulation Design to compare and contrast quantitative results- diagnostic test and audio recording tests, with qualitative findings- observation. The data analyzed by using SPSS version 23 and descriptive analysis. Finally, this study recommended some pedagogical and teaching and learning procedures to be used in the classes to develop Omani EFL learners’ pronunciation of /p/ and /ʧ/ consonant sounds.